2009
DOI: 10.1242/jeb.027862
|View full text |Cite
|
Sign up to set email alerts
|

Post-prandial metabolic alkalosis in the seawater-acclimated trout: the alkaline tide comes in

Abstract: SUMMARYThe consequences of feeding and digestion on acid-base balance and regulation in a marine teleost (seawater-acclimated steelhead trout; Oncorhynchus mykiss) were investigated by tracking changes in blood pH and [HCO 3 -], as well as alterations in net acid or base excretion to the water following feeding. Additionally the role of the intestine in the regulation of acid-base balance during feeding was investigated with an in vitro gut sac technique. Feeding did not affect plasma glucose or urea concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 36 publications
(43 reference statements)
4
30
1
Order By: Relevance
“…Under these circumstances, ammonia liberated from post-prandial catabolic processes would begin to accumulate in the plasma and eventually translate into elevated rates of ammonia excretion, as was the case in the present study. This pattern is also observed in other ammoniotelic teleosts following feeding (Kaushik and Teles, 1985;Kaushik and Gomes, 1988;Alsop and Wood, 1997;Wicks and Randall, 2002;Bucking and Wood, 2008;Bucking et al, 2009;Zimmer et al, 2010). In addition, this explanation also clarifies why the increases in plasma ammonia levels (Fig.1B) and ammonia excretion rates (Fig.1A) observed in crowded and unconfined fish during the post-prandial period were of similar magnitude.…”
Section: The Effects Of Feeding On Nitrogen Excretionsupporting
confidence: 76%
See 1 more Smart Citation
“…Under these circumstances, ammonia liberated from post-prandial catabolic processes would begin to accumulate in the plasma and eventually translate into elevated rates of ammonia excretion, as was the case in the present study. This pattern is also observed in other ammoniotelic teleosts following feeding (Kaushik and Teles, 1985;Kaushik and Gomes, 1988;Alsop and Wood, 1997;Wicks and Randall, 2002;Bucking and Wood, 2008;Bucking et al, 2009;Zimmer et al, 2010). In addition, this explanation also clarifies why the increases in plasma ammonia levels (Fig.1B) and ammonia excretion rates (Fig.1A) observed in crowded and unconfined fish during the post-prandial period were of similar magnitude.…”
Section: The Effects Of Feeding On Nitrogen Excretionsupporting
confidence: 76%
“…Higher hepatic Rh mRNA expression was accompanied by an upregulation of both Rhcg1 and Rhcg2 at the gill (Fig.5A). This scenario is similar to that of most teleosts that simply excrete the majority of excess ammonia across the gills (Kaushik and Teles, 1985;Wicks and Randall, 2002;Bucking and Wood, 2008;Bucking et al, 2009). Indeed, physiological data from the present study confirmed that unconfined toadfish excreted the majority of their wastes as ammonia (Table2), and also had higher rates of ammonia excretion than their crowded counterparts.…”
Section: The Effects Of Feeding On Nitrogen Excretionsupporting
confidence: 67%
“…However, following direct evaluation of these two methods, we found [ 14 C] PEG to be inconsistent and unreliable for most species. The average rates of net fluid absorption by gut sacs measured directly using the gravimetric method from all five species compared favourably with previous studies under similar conditions (Mainoya and Bern, 1982;Marshall et al 2002;Grosell et al 2005;Bucking et al 2009). Net fluid absorption measured simultaneously by [ 14 C] PEG was on average 2-7 times higher in the toadfish intestine (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…Here, the most obvious interpretation for the observed protection by feeding against metal accumulation is that the ingestion, digestion and assimilation of food prevents the uptake of waterborne metals in the gastro intestinal tract by decreasing the drinking of water (Wood et al 2010) and/or changing the physico−chemical environment of the intestines (e.g. pH and acid−base disturbances [Taylor et al 2007, Bucking et al 2009], gut fluid volume [Wood et al 2010], bulk ion exchange and ion concentration [Bucking et al 2011]). Alternatively, it is noteworthy that the fish in all these studies (including the present study) were fasted for >10 d, which usually resulted in an insufficient intake of essential nutrients, thus resulting in po tential disturbances in normal phy siological processes/functions, such as energy metabolism and partitioning (Sun et al 2003), osmoregulation (e.g.…”
Section: Starvation and Waterborne CD Bioaccumulationmentioning
confidence: 99%
“…Since most marine fish drink seawater continuously to maintain osmotic homeostasis (Grosell 2006) and intestines are the major sites for the uptake of dissolved metals (Zhang & Wang 2007a), feeding and digestion can alter the waterdrinking rate (Wood et al 2010) and physico-chemical environment of fish intestines (e.g. pH and acid−base levels [Taylor et al 2007, Bucking et al 2009] and major ion concentrations [Bucking et al 2011]). For instance, Wood et al (2010) found that gulf toadfish Opsanus beta under daily satiation feeding accumulated much less waterborne Ag in whole body, liver and white muscle samples than those without feeding.…”
Section: Introductionmentioning
confidence: 99%